2021
DOI: 10.3762/bjoc.17.166
|View full text |Cite
|
Sign up to set email alerts
|

In-depth characterization of self-healing polymers based on π–π nteractions

Abstract: The self-healing behavior of two supramolecular polymers based on π–π-interactions featuring different polymer backbones is presented. For this purpose, these polymers were synthesized utilizing a polycondensation of a perylene tetracarboxylic dianhydride with polyether-based diamines and the resulting materials were investigated using various analytical techniques. Thus, the molecular structure of the polymers could be correlated with the ability for self-healing. Moreover, the mechanical behavior was studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…It has been reported that increased electron density distribution around the aromatic ring leads to a higher bond strength, leading to a shi to a higher wavenumber. 86 Therefore, the observed shi of the aromatic C]C bond wavenumber in TFP-Py and TFP-BF 3D COFs upon RhB adsorption can be attributed to the increase in the electron density distribution within the COFs due to p-p stacking interactions. As the aromatic rings of the RhB molecule come close to the aromatic rings of the COFs, there can be a redistribution of electron density between them.…”
Section: Dye Adsorption: Kinetics and Reusabilitymentioning
confidence: 96%
“…It has been reported that increased electron density distribution around the aromatic ring leads to a higher bond strength, leading to a shi to a higher wavenumber. 86 Therefore, the observed shi of the aromatic C]C bond wavenumber in TFP-Py and TFP-BF 3D COFs upon RhB adsorption can be attributed to the increase in the electron density distribution within the COFs due to p-p stacking interactions. As the aromatic rings of the RhB molecule come close to the aromatic rings of the COFs, there can be a redistribution of electron density between them.…”
Section: Dye Adsorption: Kinetics and Reusabilitymentioning
confidence: 96%
“…The excellent physicochemical properties of graphene allow it to contribute to various functional roles during the healing process [29]. For extrinsic self-healing, such as the type carried out in this work, the six-membered carbon structure of graphene in general allows it to attract the repair agents through π-π electron interactions, and the presence of healing agents containing oxygen groups also have adsorption sites for various graphene derivatives, such as GNP [30]. As graphene is an excellent conductor of electricity, due to its unique two-dimensional structure, when the GNPs are added to the coating containing the MCs, a more conductive network within the matrix may then be created compared to the MCs with no GNPs [29,31].…”
Section: Self-healing and Corrosion Resistance Of The Coatingmentioning
confidence: 99%
“…The most important factors for using supramolecular interactions for self-healing are their strength (resulting either in a stronger or weaker supramolecular network) and the dynamics of the self-healing processes (reestablishing the broken bonds after damage) [47,48]. Supramolecular interactions include hydrogen bonds [24,[48][49][50], metal-ligand coordination [51], electrostatic (ionic) interactions [52], host-guest interactions [53], π-π stacking [54,55], dipole-dipole interactions [56] and van der Waals interactions [32]. Self-healing via dynamic covalent bonds can generally be achieved by shifting the equilibrium from an energetically higher to an energetically lower state.…”
Section: Self-healing Mechanismmentioning
confidence: 99%